2018
DOI: 10.1002/jcb.27754
|View full text |Cite
|
Sign up to set email alerts
|

Erbin plays a critical role in human umbilical vein endothelial cell migration and tubular structure formation via the Smad1/5 pathway

Abstract: Angiogenesis is an important process in atherosclerosis. ErbB2 was proved to have an important role in vascular development, but it is still unclear whether Erbin expresses in vessels as well as its location and function in the vessels. In the current study,we investigated the location and function of Erbin in human umbilical veins. The human umbilical veins were prepared, and immunofluorescent analysis was performed to determine the expression of Erbin. Human umbilical vein endothelial cells (HUVECs) were cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Other than evidence for an interaction of erbin with integrin β4 in hemidesmosomes, it has few published links to adhesome components, and a potential role in IAC regulation has yet to be explored (Favre et al, 2001). Like scribble, erbin has been localized to the leading edge of cells and was identified in the meta-adhesome (one of seven datasets; Jin et al, 2019;Dan et al, 2010;Horton et al, 2015). However, considering that erbin is identified as a proximal interactor by a different subset of adhesome baits, and is not detected by BirA*-β-Pix and -GIT1, it is likely that the two proteins have different binding partners and perform different roles.…”
Section: Topological Organization Of the Proximity-dependent Adhesomementioning
confidence: 99%
“…Other than evidence for an interaction of erbin with integrin β4 in hemidesmosomes, it has few published links to adhesome components, and a potential role in IAC regulation has yet to be explored (Favre et al, 2001). Like scribble, erbin has been localized to the leading edge of cells and was identified in the meta-adhesome (one of seven datasets; Jin et al, 2019;Dan et al, 2010;Horton et al, 2015). However, considering that erbin is identified as a proximal interactor by a different subset of adhesome baits, and is not detected by BirA*-β-Pix and -GIT1, it is likely that the two proteins have different binding partners and perform different roles.…”
Section: Topological Organization Of the Proximity-dependent Adhesomementioning
confidence: 99%
“…ERBB2IP is a member of the leucine-rich repeat sequence and PDZ structural domain protein family and has a protective effect on cardiomyocyte apoptosis under the stimulation of catecholamines, 13 and it has been reported that ERBB2IP can promote angiogenesis. 14 Using the transcriptome dataset reported in a previous study, 11 we analyzed the circRNA expression profiles of neonatal and adult mouse hearts and screened the circRNA circERBB2IP, which is a circRNA containing 364 bases. It is produced by the head-to-tail splicing of exons 2, 3, and 4 of the parental gene ERBB2IP.…”
Section: Resultsmentioning
confidence: 99%
“…To detect cellular activity and proliferation, live/dead cell staining (BestBio, Shanghai, China) and CCK-8 assay (Bioss, Beijing, China) were performed. As described in previous experiments ( Jin et al, 2019 ), the medium required for the experiment was endothelial cell medium (Sciencell Research Laboratories, China). Empty titanium (eTi), hydrogel-bound titanium (cTi), and hydrogel-bound titanium scaffolds loaded with VEGF (cTi/VEGF) were placed into 24-well plates.…”
Section: Methodsmentioning
confidence: 99%